PEMANFAATAN RESIDU ABU SERBUKGERGAJI DAN KASCING PADA MEDIUM GAMBUT SETELAH PENANAMAN TOMAT UNTUK PENANAMAN BAWANGMERAH - Murniati '; Fetmi Silvina; Anthony Hamzah (Universitas Riau, 2010)
Tliis research was conducted to determine tbe residue efTect of sawdust ash and worm compost inpeat medium after tomato pbinting on the growth and yield of shallot This research was carried out in thegreen bouse of Faculty ofAgriculture, Riau University. The design was Complete Randomized Design (CRD),with four factors and three replications. The first factor was residue of sawdust ash after tomato plantingwhich consisted of four levels (0,10,20 and 30 ton/ha) and tbe second factor was resklue of worm compostafter tomato planting with four levels (0,5,10 and 15 lon^a). The result showed that the residue of sawdustash and worm compost had positivecRect on the growth and yield ofshaHot The highest result was found forresklue of 30 ton/ha sawdust ash and tO ton/ha worm compost after tomato planting.